Peranan Tipografi Ramah Lingkungan Dalam Desain Kemasan UMKM di Kabupaten Banyumas - Natalia Ira Kartika; Yosita Lianawati; Ria Manurung (Besaung : Jurnal Seni Desain dan Budaya, 2026)
This study examines how environmentally friendly typography plays a role in sustainable packaging design for micro, small, and medium enterprises (MSMEs) in Banyumas Regency. The research is motivated by the tendency of MSME packaging design practices to focus primarily on the use of environmentally friendly materials, while visual elements particularly typography have not yet been regarded as a strategic component of sustainability. In fact, typographic choices influence readability, ink efficiency, production processes, and consumers’ perceptions of a product’s environmental value. The aim of this study is to identify the types of typography used in MSME packaging and to analyze the concept and role of environmentally friendly typography as a sustainable design strategy. This research employs a descriptive qualitative method with a design approach. Data were collected through in-depth interviews with MSME actors, designers, and consumers, as well as visual observations of more than 100 food and beverage packaging samples. The analysis was conducted thematically and supported by descriptive statistics. The findings indicate that 47% of packaging still uses decorative typefaces, 22% demonstrate low readability, and 66% do not apply typographic consistency. Conversely, more than 60% of respondents acknowledge that typography influences perceptions of sustainability. This study formulates four metrics for environmentally friendly typography: readability, visual efficiency, information hierarchy, and typographic consistency. Therefore, environmentally friendly typography can function as an integrative sustainable design strategy in the packaging of micro, small, and medium enterprises (MSMEs) in Banyumas